Innovation Analytics : Tools for Competitive Advantage - Subramanian, Nachiappan, editor 656340; Ponnambalam, S. G. (Sivalinga Govinda), editor 656341; Janardhanan, Mukund, editor 656342; World Scientific (Online service) 655444 (New Jersey : World Scientific)
"Innovation analytics is an emerging paradigm that integrates information/knowledge, analytics, digital twins and artificial intelligence to support and manage the entire lifecycle of a product and process from inception, through engineering design and manufacture, to service and disposal of manufactured products. Innovation analytics is to become an integral part of the innovation lifecycle to help make smart, agile decisions and accelerate business growth. Innovation Analytics: Tools for Competitive Advantage provides a comprehensive overview of the challenges and opportunities behind: The latest research behind technological advances driving innovation analytics The transition of analytical ideas to interdisciplinary teams The development of deep synchronicity of skills and production innovation The use of innovation analytics in multiple stages of product and process evolution beneficial to students, scientists, engineers, academics, and management professionals In exploring the impact of emerging developments in the current climate, researchers and academics will be able to gain insights into real-world usage of analytics for innovation and contribution toward society"--